A leopard diary : my journey into the hidden world of a mother and her cubs - Eszterhas, Suzi (Owlkids Books, 2022)
Wildlife photographer Suzi Eszterhas takes readers on a journey with her as she follows a mother leopard who gives birth to cubs and raises them on a wildlife reserve in Botswana. With help from her guide Kambango, Eszterhas is able to document poignant moments from the mother's days with her cubs in diary entries. Includes dozens of color photographs, an interview with Kambango, and a glossary.